Epidemiology of stroke in the south west of Iran: A cohort study - Sudabeh Mohamadi; Sudabeh Mohamadi; Niloofar Motamed; Afshin Ostovar; Reza Nemati (Shahid Beheshti University of Medical Sciences, 2017)
Background: Stroke is the second common cause of death in the world. It imposes a huge amount of economic and social burden on individuals, families, communities, and governments. There are significant regional differences in stroke incidence even within countries. The last information about stroke incidence in Bushehr is related to 2002-2003. Life expectancy is increasing and as a result burden of non-communicable diseases including stroke is in progress, so the current study was conducted to obtain a better picture of stroke incidence in Bushehr district, Iran, in 2013-2014.   Methods: In a retrospective cohort study, hospital files of all the individuals admitted as stroke or transient ischemic attack in the Persian Gulf and Salman-e-Farsi Hospitals in 2013-2014 were studied. A list of patients with diagnosis of stroke was prepared using International Classification of Disease 10. Bushehr middle year population was estimated based on the census (2011-2012). Age standardization was done according to World Health Organization standard population. Incidence correction was done using sensitivity analysis.     Results: In the study year, 255 cases of stroke were registered in two hospitals. The mean age was 65.3±14.14 years. Crude and standardized incidence of stroke were 92.71 (81.69-104.81) and 198.3 (189.68-207.22) per 100,000, respectively. Standardized incidence was higher in men as compared with women (P<0.001).   Conclusion: Stroke incidence is high, especially in men, in Bushehr district. A population-based stroke registry is necessary for more accurate estimation of the rates over time.